2003
DOI: 10.7589/0090-3558-39.4.779
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Ruminant Alpha-Herpesviruses and Pestiviruses in Norwegian Cervids

Abstract: A serologic survey revealed that Norwegian populations of free-ranging reindeer (Rangifer tarandus tarandus), roe deer (Capreolus capreolus), red deer (Cervus elaphus), and moose (Alces alces) have been exposed to alpha-herpesviruses and pestiviruses. A total of 3,796 serum samples collected during the period 1993-2000 were tested in a neutralization test for antibodies against bovine herpesvirus 1 (BHV-1) or cervid herpesvirus 2 (CerHV-2), and 3,897 samples were tested by a neutralization test and/or enzyme-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
53
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 30 publications
6
53
0
Order By: Relevance
“…A Norwegian investigation showed similar results: 60% of reindeer and 15% of calves were shown to be seropositive [55]. In Norway, during the period 1993-2000, antibodies against BoHV-1 related alphaherpesviruses were found in 28.5% of reindeer [70]. These results indicate that alphaherpesvirus infections are endemic in reindeer and that CvHV-2 is most likely the herpesvirus responsible for the observed prevalences.…”
Section: Cervid Herpesvirusmentioning
confidence: 56%
“…A Norwegian investigation showed similar results: 60% of reindeer and 15% of calves were shown to be seropositive [55]. In Norway, during the period 1993-2000, antibodies against BoHV-1 related alphaherpesviruses were found in 28.5% of reindeer [70]. These results indicate that alphaherpesvirus infections are endemic in reindeer and that CvHV-2 is most likely the herpesvirus responsible for the observed prevalences.…”
Section: Cervid Herpesvirusmentioning
confidence: 56%
“…Experimentally it has been demonstrated that CvHV-2 can infect bovines and cause a mild rhinotracheitis, but no latency of CvHV-2 has been detected in bovines (18,34). Serological evidence of CvHV-2 infection has been reported for both wild (13) and semidomesticated (31,36) reindeer (Rangifer tarandus tarandus) in Norway, for barren-ground caribou (Rangifer tarandus groenlandicus) in Greenland (4), and for Grant's caribou (Rangifer tarandus granti) in Alaska (8).…”
mentioning
confidence: 96%
“…Although restricted to Germany, this is the first survey of European NP for the presence of antibodies to viral diseases in cervids. Results from previous studies have revealed antibodies to some of these agents in free-ranging deer elsewhere in Germany and in other European countries (e.g., Weber et al, 1978;Thiry et al, 1988;Liebermann et al, 1989;Thiry et al, 1992;Frö lich, 1996;Pospisil et al, 1996;Lillehaug et al, 2003). Results presented in this report for the three a-herpesviruses are in accordance with those reported previously for freeranging deer elsewhere in Germany Frö lich, 1996;Mü ller et al, 1996Mü ller et al, , 1997.…”
mentioning
confidence: 96%